Diversifikasi Transmisi Bahasa Agama Dalam Konteks Politik; Tinjauan Linguistik Strukturalis Terjemah Kata “Auliya’” - Huda, Muhammad Muchlis; Qalyubi, Syihabuddin; Ahmadi, Ahmadi; Evi Muafiah, Evi Muafiah; Jailani, Mohammad (Kalimatuna: Journal of Arabic Research, 2023)
In the last few decades, especially after the fall of the New Order regime, the political constellation in Indonesia has been quite dynamic and tends to be populist. Many people consider that the populism aspirations of Muslims as the majority religion embraced by Indonesian citizens in several aspects of political life are experiencing a strengthening trend. One of the precedents that indicates the strengthening trend of Islamic populism is the case of blasphemy and the emergence of the 212 movement. This movement emerged after the 2017 DKI Jakarta election campaign where one of the candidate pairs at that time was suspected of insulting Islam by quoting Tarjamah Surah al-Maidah Verse 51 for pragmatic purposes of electoral politics. The question is, how do translation institutions in Indonesia that are considered authoritative translate this verse, especially the word "auliya". This study focuses its discussion on the presentation of tarjamah data for the word "Auliya'" which is contained in the work of Tarjamah Ministry of Religion of the Republic of Indonesia and Tarjamah Tafsiriyah M. Thalib. The results of this study indicate that the differences that occur between the translations of the two translations are very diametrical. The translation of the word "auliya'" in the Tarjamah M. Talib uses a more fundamental diction when compared to the tarjamah of the Indonesian Ministry of Religion. The Tarjamah Ministry of Religion of the Republic of Indonesia chose to use the term "friend". Tarjamah M. Talib prefers to use the term "leader".